Using farm typology to deliver smarter, tailored fertiliser solutions in Rwanda - Mudereri, B.T.; Benimana, Gilberthe Uwera; Kihoro, E.; Cyamweshi, A.; Kayumba, J.; Assefa, B.; Senthilkumar, Kalimuthu (2025)
This report applies a farm typology approach to design smarter, tailored fertiliser recommendations for smallholder farmers in Rwanda. Using nationally representative survey data, the study identifies four distinct farm types that differ in resource endowment, crop specialisation, input use, and vulnerability. The findings demonstrate that uniform fertiliser policies fail to address this heterogeneity, while typology-based recommendations can improve nutrient use efficiency, productivity, profitability, and sustainability. The report provides actionable pathways for differentiated fertiliser advice, extension services, and policy design to support inclusive and climate-resilient agricultural intensification in Rwanda.